Waste Disposal Efforts and Policies in BPSDM Kemendagri Jakarta - Falah, TR. Fahsul; Jamil, MH; Demmalino, EB; Arsal, A; Sulistyowati, Lilik; Herlina, R Lisye; Sari, Yenita Sandra (Universitas Tanjungpura, 2024)
Offices as one of the waste-producing locations have contributed to the volume. Challenges in waste management strategies differ between formal and non-formal institutions. Waste management needs a collaborative management strategy in its management. An effective waste management strategy as a solution to improve employee performance in implementing waste management regulations. This study aims to analyze Collaborative management with an office waste management strategy at the BPSDM Kemendagri Jakarta office. Collaborative management to manage environmental problems, especially waste generated from activities on weekdays. Waste management regulations need to be upgraded to become policies in the Ministry of Home Affairs offices. The method used in this study is descriptive qualitative with literature review and survey techniques. Collaborative management in office waste management is not optimal. a policy proposal for a waste management strategy and for responding to contextual changes involving the problem of formal government office waste. This finding has implications for being a policy proposal for a waste management strategy and for responding to contextual changes involving the problem of formal government office wastesustainable.